Black phosphorus saturable absorber for Q-switched technique pulse generation - Hussein, Liban; Hamida, Belal Ahmed; Eltaif, Tawfig; Khan, Sheroz; Habaebi, Mohamed Hadi; Harun, Sulaiman Wadi (IEEE Explore, 2017)
This paper reported a passive Q-switched erbium doped fiber laser (EDFL) using two-dimensional (2D) material of black phosphorus saturable absorber (BP-SA). The maximum output power reached is 3.54 mW, which is generated by pump power of 42.327 mW. The results show that, a stable pulse was generated with repetition rate starts at about 9.606 kHz and ends at about 44.72 kHz, and very narrow pulse width between 40.01 μs and 9.84 μs and pulse energy 80 nJ. Clearly, the stability of the Q-switched pulse train was achieved because the BP-SA film was inserted in the laser ring cavity.